Comparing Hemodialysis and Peritoneal Dialysis Patients for Gastrointestinal Symptoms - Muhammad Affan Qaiser, Batool Butt, Farooq Ahmed, Neha Niaz, Niaz Ahmed, Ghulam Muhammad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research was to compare gastrointestinal (GI) symptoms in ESRD patients receiving PD and HD to see whether there were any significant changes. Methods: After the ethical approval from the institute review board, this crossectional study was conducted at shahida Islam medical complex ,lodhran. From 01/01/22 to 30/06/22. A modified 15-item gastrointestinal symptom rating scale (GSRS) questionnaire was used to assess GI symptoms; this questionnaire included questions on eating dysfunction. Age, a etiology of ESRD, and most recent adequacy evaluation of dialysis were collected through the follow-up database, patient interviews, and chart reviews. Results: Total seventy patients were included in the present study, N=35 was on hemodialysis and N=35 on peritoneal dialysis. HD and PD patients were similar with respect to age, sex, the occurrence of diabetes mellitus, and average dialysis duration. In ESRD patients’ overall prevalence of GI symptoms (GSRS >1) was 68.5% (48/70 patients). Patients with a GSRS > 1 were more common among those with HD group (28/35; 80%) than those with PD (57%; 20/35) (P 0.058*). In the HD group, more patients suffered from abdominal pain, constipation, and diarrhea (74%, 60% and 68.5%, respectively), compared with those in the PD group (34%, 28.5% and 32%, respectively; P value is 0.003, 0.001, and 0.008 respectively) Conclusion: Gastrointestinal (GI) symptoms vary in frequency, intensity, and variety across HD and PD individuals. Keywords: Gastrointestinal symptom, Hemodialysis, Peritoneal dialysis, End-stage renal disease